Dinâmica costeira e a trama complexa entre natureza e sociedade nas praias da Penha e do Seixas‐PB - Silva, Cláudia Simoni Velozo da (2009)
The coastline of the municipality of João Pessoa (PB) extends for about 25 km, consisting of a succession of open bays and sandy spits cuspate foreland, these generally associated to the shelter of the rocky reefs (beach rocks) and / or seaweed / coral reefs. Similar to other coast regions of the globe, the coast of Paraíba shows processes of coastal erosion at various levels, resulting from a complex web that links natural and social elements. This research aims to comprehend and quantify the variations of coastal dynamic on the beaches of Seixas and Penha-PB, as well as, interference from the relation between society and nature in this environment, with reference to the process of urbanization and tourism in João Pessoa. The theoretical and conceptual basis is based on the systems theory, in the discussion of the relation of hostile reciprocity between society and nature, in order to understand the origins of environmental degradation, especially of coastal erosion on these beaches. The methodological procedures used for preparation of this work were: survey on specific literature and documents, stages of field and laboratory. The literature review focused on the search for and understanding of the concepts of nature, complexity and place. As well, we research the current concepts that permeate the literature inherent in Coastal Geomorphology, seeking dialogue with authors of Geography and related fields. The stages of field and laboratory were complementary, at this stage we monitor the vertical morphological variations of short-term (Beach Profile), from three points along these beaches, raised data related to the hydrodynamic (wave height, wave period, speed of coastal current, direction of the current drift, wind speed, temperature, and humidity), we collected sediment samples in three beach compartments (shoreface, foreshore and backshore) for then, in the laboratory, we carry out the analysis of sediments, finally, designed the characterization of the natural elements that influence coastal dynamics. The above-mentioned survey covered: geology, geomorphology, soils, vegetation, hydrography, and the elements of weather. With regard to social aspects, we discuss the process of urbanization in the coastal area of João Pessoa with emphasis on human settlements and its environmental impacts on the edge; we treat the tourist attraction rate on the beaches of Penha and Seixas through interviews and questionnaires conducted with tourists, travel agents and locals, which amounted a total of 65 questionnaires on the beach of Penha and 75 at beach of Seixas, where the main objective was to determine the origin of locomotion of this public and the elements which attract them to those beaches. The compiled data showed a erosive tendency for these beaches, where the uncontrolled urban occupation of the coastal zone and the tourism contribute to aggravate the problem, as the urban elements occupy areas belonging to coastal dynamics and do not comply with environmental laws.